Xylophone music of Uganda: theembaire of Nakibembe, Busoga - Micklem, James; Cooke, Andrew; Stone, Mark (International Library of African Music, 1999)
The amadinda and akadinda xylophone music of Buganda1 2 have been well described in the past (Anderson 1968). Good players of these xylophones now seem to be extremely scarce, and they are rarely performed in Kampala. Both instruments, although brought from villages in Buganda, formed part of a great musical tradition associated with the Kabaka's palace. After 1966, when the palace was overrun by government forces and the kingdom abolished, the royal musicians were cut off from their traditional role.
Keywords: Xylophone; Xylophone music; African Music; Uganda; Xylophone (Instrument)